Analisis Minat Belajar Siswa Melalui Model Pembelajaran Teams Games Tournament pada Materi Logaritma SMK - Andinasari, Andinasari; Agustin, Sintia; Sistyawati, Risda Intan (Supermat : Jurnal Pendidikan Matematika, 2024)
The purpose of this study was to analyze the learning interest of SMK Negeri 1 Prabumulih students on logarithm material through the Teams Games Tournament (TGT) learning model. The research methodology used is descriptive qualitative. Thirty-one students from class X Accounting 2 were selected as research subjects for this study. Questionnaires about students' interest in learning which included 15 positive and negative statements served as the research instrument. Microsoft Excel was used to process data from the answers given by students on the questionnaire. The research findings indicate that students' enthusiasm in learning is 79,76%, which falls into the Strong group, when looking at the average percentage of all indicators. As a result, it can be concluded that the Teams Games Tournament (TGT) learning model on logarithm material was successful in encouraging students in class X Accounting 2 at SMK Negeri 1 Prabumulih to respond positively to their mathematical lessons.